2009
DOI: 10.1002/cncr.24717
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns of aging Americans with differentiated thyroid cancer

Abstract: BACKGROUND:The incidence of differentiated thyroid cancer (DTC) increases with age. Total thyroidectomy, often followed by radioactive iodine (RAI), is recommended for patients who have tumors that measure !1 cm in greatest dimension. In the current study, the authors assessed the use of thyroidectomy and RAI among elderly patients with DTC and the effects on survival. METHODS: Adults aged !45 years with DTC !1 cm in the Surveillance, Epidemiology, and End Results database from 1988 to 2003 were included. Biva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 52 publications
4
32
1
1
Order By: Relevance
“…In the present study, no significant difference was observed in primary tumor volumes between the two age groups, which is consistent with the reported literature 14. In contrast to patients aged below 60 years, the pathological positive neck nodes were significantly higher in patients aged above 60 years, owing to the presence of lymphovascular space invasion, multifocality, and aggressive histopathological variants in elderly patients, which supports the routine use of lateral neck dissection in this age group 15,16…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, no significant difference was observed in primary tumor volumes between the two age groups, which is consistent with the reported literature 14. In contrast to patients aged below 60 years, the pathological positive neck nodes were significantly higher in patients aged above 60 years, owing to the presence of lymphovascular space invasion, multifocality, and aggressive histopathological variants in elderly patients, which supports the routine use of lateral neck dissection in this age group 15,16…”
Section: Discussionsupporting
confidence: 92%
“…(22) However, it was previously demonstrated that elderly patients with differentiated thyroid cancers receive less aggressive surgical and radioactive iodine treatment than younger patients, despite having more advanced disease and improved survival associated with treatment. (17) Successful surgery for thyroid cancer has been shown to not only increase the survival rate but also improve the quality of life of older patients. (23) It is generally perceived that the elderly may have increased operative risks because of the presence of increasing number of comorbidities, thus leading to a more conservative or non-operative approach to be adopted in these patients with thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…(9–16) However, current data show that older patients with thyroid cancer are less likely to receive guideline concordant care. (17) Additionally, older age and Medicare insurance were found to be independently associated with less aggressive management of patients with high-risk thyroid cancer. (18)…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that older patients are less likely to receive total thyroidectomy [24], be referred for specialist surgical care involving travel of a large distance [25], or receive treatment with radioiodine [24,26]. It is unclear whether these differences reflect difficulty of access to treatment for older patients, a bias in clinicians against aggressive treatment with increasing age, or use of individualised risk-benefit decision making leading to less aggressive therapy.…”
Section: Age and Thyroid Cancer Prognosismentioning
confidence: 97%